POLA HUBUNGAN ANTARA NELAYAN PEMILIK MODAL DENGAN NELAYAN BURUH DI NAGARI SUNGAI TUNU BARAT KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Cahyunengsih, Neri - (Pendidikan Sosiologi, 2014)
In the background of the problem in the research, it explained that the people who as the fisherman would found many risks in working. This job makes the people unsatisfied with the earning of this job. The fisherman only has a simple ship but they must endure with this condition for their. The purpose of this research is to describe about the correlation between the fisherman an the financier and the fisherman as the worker at Nagari Sungai Tunu Barat Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan. This research is supported by George C. Homans, he stated that an exchange of social. The kinds of data wore primary data and secondary data. The instrumentation of this research were (1) observation (non-participant) (2) unstructure interview (3) documentation. In this research, the correlation between the fisherman as the financier and the fisherman as the worker includes of (1) in economy (2) in social, There were (a) the worker owed the money to the financier for a living family (b) the correlation between the fisherman as the financier and the fisherman as worker, because of they must help to each other.